“Another brick in the WALL”: Wiki Assisted Language Learning in ESP university courses - Hadjiconstantinou, Stavroulla; Yerou, Christina (My University, 2010)
In an effort to achieve high competence in languages, the Cyprus University of Technology (CUT) offers courses of English for Specific Academic Purposes (ESAP). These courses are tailored to the academic and professional needs of the students of the ten departments of the university. Furthermore, English courses offered at the university are designed in such a way as to combine face-to-face instruction with a CALL component, in other words blended learning. Such practice has been shown to promote student autonomy and empowerment. ICT tools incorporated in the courses were, among others, Word processing and presentation tools, the Internet, and YouTube. In a recent evaluation research study conducted by the Language Centre (LC) of the university, students identified the use of the aforementioned ICT tools as extremely essential in their learning especially because these can be used to cater for their most important needs. For example, “searching the internet for information” and “reading and understanding online material in English” were identified as two of the most needed skills by the students, who found that these were covered in their English courses. The results from the study confirmed that ICT skills such as using online dictionaries and preparing presentations were greatly improved through CUT English courses, which demonstrated that the ICT component was a big asset and one which could perhaps be exploited even further. This led us to consider the integration of wikis in our courses. Wikis were chosen due to their great potential educational value, which has become apparent in the recent years. Besides, they combine multiple applications and tools already used in CUT courses. This paper will show samples of ESAP wikis through which the benefits and challenges of this web 2.0 tool will be discussed. Reflections of students on the use of this revolutionary tool will be presented.